Embryotoxic and genotoxic effects of heavy metals and pesticides on early life stages of Pacific oyster (Crassostrea gigas) - Mai, Hong Ngoc; Cachot, J.; Brune, J.; Geffard, Olivier; Belles, A.; Budzinski, H.; Morin, Brice (Marine Pollution Bulletin, 2012)
[Departement_IRSTEA]Eaux [TR1_IRSTEA]BELCA International audience This study evaluated embryotoxicity and genotoxicity of two dissolved metals copper and cadmium (Cu and Cd) and two pesticides (metolachlor and irgarol) occurring in Arcachon Bay (SW France) in Pacific oyster (Crassostrea gigas) larvae and investigated the relationship between those two endpoints. Embryotoxicity was measured by calculating the percentage of abnormal D-shaped larvae and genotoxicity was evaluated with DNA strand breaks using the comet assay. After 24 h exposure, significant increases of the percentage of abnormal D-larvae and the DNA strand breaks were observed from 0.1µg/L for Cu, 10 µg/L for Cd and 0.01 µg/L for both irgarol and metolachlor in comparison with the controls. A strong positive relationship between embryotoxicity and genotoxicity was recorded for Cu, Cd and metolachlor. The current study suggests that copper, irgarol and metolachlor can induce larval abnormalities and DNA damage in a population of exposed oysters at environmentally relevant concentrations.